2019
DOI: 10.1088/2515-7639/aaed4c
|View full text |Cite
|
Sign up to set email alerts
|

Belousov–Zhabotinsky reaction in liquid marbles

Abstract: In Belousov-Zhabotinsky (BZ) type reactions, chemical oxidation waves can be exploited to produce reaction-diffusion processors. This paper reports on a new method of encapsulating BZ solution in a powder coating of either polyethylene (PE) or polytetrafluoroethylene (PTFE), to produce BZ liquid marbles (LMs). BZ LMs have solid-liquid interfaces compared to previously reported encapsulation systems, BZ emulsions and BZ vesicles. Oscillation studies on individual LMs established PE-coated LMs were easier to pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 115 publications
(163 reference statements)
0
23
0
1
Order By: Relevance
“…This approach enables us to transfer and manipulate the BZ LM controller without wetting the underlying surface. Our scoping studies showed that the BZ media encapsulated in LMs exhibits 'classical' chemical excitation wave patterns, with mainly trigger waves observed [13]. The BZ media has been reported to be sensitive to illumination.…”
Section: Introductionmentioning
confidence: 71%
“…This approach enables us to transfer and manipulate the BZ LM controller without wetting the underlying surface. Our scoping studies showed that the BZ media encapsulated in LMs exhibits 'classical' chemical excitation wave patterns, with mainly trigger waves observed [13]. The BZ media has been reported to be sensitive to illumination.…”
Section: Introductionmentioning
confidence: 71%
“…The range of potential applications for LMs is huge and spans most fields of life sciences, chemistry, physics and engineering [8,35,15,5,12]. Previously, we demonstrated BZ marbles support non-trivial patterns of chemical oscillations [18].…”
Section: Introductionmentioning
confidence: 98%
“…The oxidation of an organic substrate, e.g. malonic acid by bromate ions in acidic medium in the presence of a single-electron transfer metal ion redox catalyst like ferroin, typically known as Belousov-Zhabotinsky reaction [25], has also been reported [26,27] in liquid marbles.…”
Section: Introductionmentioning
confidence: 99%